Thiophenolato-bridged dinuclear arene ruthenium complexes: a new family of highly cytotoxic anticancer agents - Gras, Michaël; Therrien, Bruno; Süss-Fink, Georg; Zava, Olivier; Dyson, Paul J. (My University, 2015)
New cationic diruthenium complexes of the type [(arene)2Ru2(SPh)3]+ , arene being C6H6, p-iPrC6H4Me, C6Me6, C6H5R, where R = (CH2)nOC(O)C6H4-p-O(CH2)6CH3 or (CH2)nOC(O)CH[double bond, length as m-dash]CHC6H4-p-OCH3 and n = 2 or 4, are obtained from the reaction of the corresponding precursor [(arene)RuCl2]2 and thiophenol and isolated as their chloride salts. The complexes have been fully characterised by spectroscopic methods and the solid state structure of [(C6H6)2Ru2(SPh)3]+, crystallised as the hexafluorophosphate salt, has been established by single crystal X-ray diffraction. The complexes are highly cytotoxic against human ovarian cancer cells (cell lines A2780 and A2780cisR), with the IC50 values being in the submicromolar range. In comparison the analogous trishydroxythiophenolato compounds [(arene)2Ru2(S-p-C6H4OH)3]Cl (IC50 values around 100 μM) are much less cytotoxic. Thus, it would appear that the increased antiproliferative effect of the arene ruthenium complexes is due to the presence of the phenyl or toluyl substituents at the three thiolato bridges.